Identification of the initial ability of high school students’ health literacy in virus - R D R Aditya; W Purwianingsih; D Priyandoko (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
Health literacy is very important to optimize the ability of people to access, process, understand, and apply health information from various media. Health information cannot be utilized properly if it is not supported by good literacy skills. This study aims to identify the initial ability of high school students' health literacy in virus. The research method used in this research is descriptive. The research subjects used were 10th-grade high school students at Garut, West Java in the academic year 2019/2020 who had learned about viruses. The sample that participated in this study amounted to 27 students. The research instrument used was a matter of health literacy in virus, amounting to 8 essay questions based on 4 health literacy indicators. According to the results of research, it can be concluded that the initial ability of students’ health literacy on virus was still in the low category. Most students have been able to access/obtain information and apply/use information relevant to health, while the ability of students to understand health information and process/appraise information relevant to health is still very low